The Effect of Thin Capitalization, Earning Management, and Institutional Ownership on Tax Avoidance - Instianti Elyana; Rusiyati, Sri; Restu Putri, Dita (Universitas Pamulang, 2025)
This research aims to determine the influence of Thin Capitalization, Earnings Management and Institutional Ownership on Tax Avoidance. This type of research is quantitative and uses secondary data with media in the form of property and real estate company financial reports taken from the Indonesian Stock Exchange (IDX). The population used in this research was 47 companies and through purposive sampling criteria 14 property and real estate company financial report samples were selected with the observation period from 2018-2022. Data processing uses eviews version 12.0. Based on the results of the tests carried out, the variables Thin Capitalization, Earning Management and Institutional Ownership simultaneously have an influence on Tax Avoidance. Partially Thin Capitalization and Earning Management have no effect on Tax Avoidance, while Institutional Ownership has an effect on Tax Avoidance.